Analisis Hukum Penyalahgunaan Keadaan (Misbruik van Omstandigheden) sebagai Suatu Bentuk Cacat Kehendak Ditinjau dari Hukum Perjanjian Indonesia - Raysah Afdila Fachriah; Nuzul Rahmayani (Pusat Riset dan Inovasi Nasional, 2026)
An agreement is a fundamental basis in civil law relations because it gives rise to rights and obligations for the parties who bind themselves. For an agreement to be valid, consent must arise from the free will of the parties without any defect of will as regulated in Articles 1320 and 1321 of the Indonesian Civil Code (KUHPerdata). In Indonesian legal practice, apart from classic defects of will such as coercion (dwang), mistake (dwaling), and fraud (bedrog), a modern form of defect of will has also developed, namely abuse of circumstances (misbruik van omstandigheden). Abuse of circumstances occurs when one party exploits the weak condition, dependency, or ignorance of the other party to obtain unfair advantage in an agreement. This research formulates the problems of how the concept of defect of will in abuse of circumstances is applied in the jurisprudence of Indonesian contract law and what are the legal consequences of abuse of circumstances in an agreement. The method used is normative legal research with a statutory approach and conceptual approach, as well as related legal literature. The conclusion of this research shows that abuse of circumstances is a modern form of defect of will recognized through doctrine and jurisprudence. The legal consequence is that the agreement can be annulled because the element of free consent is not fulfilled. This legal consequence provides protection for the aggrieved party and confirms that the principle of freedom of contract is not absolute, but is limited by good faith, propriety, and balance.